Evangelism and resistance in the Black Atlantic, 1760-1835 - May, Cedrick, 1969- (Book collections on Project MUSE., 2008)
This study focuses on the role of early African American Christianity in the formation of American egalitarian religion and politics. It also provides a new context for understanding how black Christianity and evangelism developed, spread, and interacted with transatlantic religious cultures of the eighteenth and early nineteenth centuries.